The Bronze and Early Iron Ages in Estonia - Lang, Valter (Estonian Archaeology, 2007)
This book analyses social, economic, and cultural processes during the Bronze and Early Iron Ages (18th century BC - 5th century AD) in what is today Estonia. The above period between the Stone Age (ca. 9000-1800 BC) and the Middle Iron Age (AD 450-800) was an era of significant and crucial developmental processes. The final transition from a foraging to a farming economy occurred during that time and resulted in an extensive settlement shift from suitable hunting and fishing places to agricultural lands. In relation to the above processes, the general settlement pattern changed, and the agricultural household as the main settlement unit became prevalent. Social relations also changed, which contributed to the development of stratified societies, at first mainly in coastal Estonia and later throughout continental Estonia. Significant developments took place both in material and intellectual culture. By the end of the period the Estonian areas had changed beyond recognition compared to what they had been at the beginning of the period.